2007
DOI: 10.1172/jci29031
|View full text |Cite
|
Sign up to set email alerts
|

Autistic-like phenotypes in Cadps2-knockout mice and aberrant CADPS2 splicing in autistic patients

Abstract: Autism, characterized by profound impairment in social interactions and communicative skills, is the most common neurodevelopmental disorder, and its underlying molecular mechanisms remain unknown. Ca 2+ -dependent activator protein for secretion 2 (CADPS2; also known as CAPS2) mediates the exocytosis of densecore vesicles, and the human CADPS2 is located within the autism susceptibility locus 1 on chromosome 7q. Here we show that Cadps2-knockout mice not only have impaired brain-derived neurotrophic factor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
214
2
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(226 citation statements)
references
References 60 publications
8
214
2
2
Order By: Relevance
“…1, item 7.7). This result, together with abnormalities in Cadps2 knockout mice and rare missense variants in patients 45 , supports a potential role for this positional candidate in disease. Similarly, a de novo loss at 20p13 (including the arginine vasopressin gene, the oxytocin gene and an additional 30 genes 4 ) is intriguing given the associations between the variation in each of the corresponding receptors and ASDs (see later section on association studies) as well as the wellestablished role of both molecules in the modulation of social behaviour.…”
Section: Copy Number Variationsupporting
confidence: 61%
“…1, item 7.7). This result, together with abnormalities in Cadps2 knockout mice and rare missense variants in patients 45 , supports a potential role for this positional candidate in disease. Similarly, a de novo loss at 20p13 (including the arginine vasopressin gene, the oxytocin gene and an additional 30 genes 4 ) is intriguing given the associations between the variation in each of the corresponding receptors and ASDs (see later section on association studies) as well as the wellestablished role of both molecules in the modulation of social behaviour.…”
Section: Copy Number Variationsupporting
confidence: 61%
“…14 Each mouse was placed in the center of an open-field apparatus (50 Â 50 Â 40 (H) cm) illuminated by light-emitting diodes (70 lux at the center of the field) and then allowed to move freely for 15 min. Distance traveled (cm) and duration (%) in the center area of the field (30% of the field) were adopted as the indices, and the relevant data were collected every 1 min.…”
Section: Open-field Testmentioning
confidence: 99%
“…Our previous studies have shown that CAPS2 is involved in the secretion of BDNF in cerebellar granule cells and cerebral cortical neurons (7,8). BDNF plays a critical role in neuronal survival and differentiation and in synaptic development and plasticity (9)(10)(11)(12).…”
mentioning
confidence: 99%